A Conceptual Framework of Enhancing Consumer Satisfaction Through Data Protection In The Postal And Telecommunications Sector In Zimbabwe. - Machengete, Gift; Sandada, Maxwell; Rumbidzai Panavanhu; Makawonesu Mandipezano; Cryford Mhaka; Lameck Chinodya; George Taruona (Acta Universitatis Danubius. Œconomica, 2024)
The purpose of the study was to develop and test a framework of data protection dimensions that enhance customer satisfaction in the Postal and Telecommunications sector. The specific objectives of the study were to establish the relationships between data protection dimensions (awareness and knowledge of the rights of data subjects, data protection trust and confidence of data subjects and cyber and data protection complaints redress) and consumer satisfaction. There has been limited study on the connection between data protection and customer satisfaction in the context of the postal and telecommunications sector. The current consumer satisfaction framework in the postal and telecommunications sector in Zimbabwe does not consider data protection issues. The study adopted a quantitative approach to establish the relationships between variables. A cross-section survey of 1,143 respondents that were randomly selected was conducted across all ten provinces in Zimbabwe. The results indicate that there is a positive relationship between consumer trust and confidence and consumer satisfaction with postal and telecommunication services. The study is crucial in informing the development of a new framework for measuring consumer satisfaction in the postal and telecommunications sector. The framework will help establish data protection metrics that have a significant influence on consumer satisfaction. Key words: Consumer trust, data subjects, complaints redress, consumer confidence, customer satisfaction. JEL Classification: M14